Analysis of Genetic Studies in Association of a and b Estrogen Receptor Gene Polymorphisms Against Endometriosis - Eldafira, Eldafira; Novitasari, Novitasari (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Endometriosis is a common cause of morbidity in women of unknown etiology. Several studies have shown endometriosis with a polygenic/multifactorial trait. To evaluate ? and ? estrogen receptor (ER) gene polymorphisms against endometriosis, this study was analyzed from an endometriosis outpatient clinic which compared 83 women with endometriosis and 76 women without endometriosis. The ER ? gene rs9340799 A/G and ER ? gene rs4986938 G/A polymorphism was identified by restriction fragment length polymorphism polymerase chain reaction. Genotype distribution and allele frequency of the +1730 G/A polymorphism in the ER ? gene rs9340799 A/G and ER ? gene rs4986938 G/A. The genetic model on the ER? rs2234693 SNP analysis that there is no significant difference in the four genetic models, but on the ER? rs498638, it appears that the genetic model dominant (GG vs (GA + AA) and co-dominant (GA vs GG + AA) showed significant differences with p less than 0.05, i.e. 0.013 and 0.06 respectively and with OR (95% CI) 0.350 and 3.258, respectively. For other genetic models, this SNP did not show significant differences. The data suggest that the ER ? gene rs4986938 G/A polymorphism can be associated with the risk of endometriosis development, regardless of the stage of the disease.